Effect of growth conditions on structure quality of KDP crystals - Salo, V.I.; Tkachenko, V.F.; Kolybayeva, M.I.; Pritula, I.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The effect of different variable crystallization parameters (supersaturation, solution acidity, degree of the solution purity, hydrodynamic growth regime) on structural quality and optical homogeneity of KDP crystals grown at the angle of synchronism θ = 59° was studied by using X-ray analysis and UV spectroscopy. It is shown that each of the chosen parameters acting in a certain way changes (with the rest being constant) the real structure and optical characteristics of crystals.